2013
DOI: 10.1002/oby.20193
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of diacylglycerol acyltransferase 1 reduces body weight and modulates gut peptide release—Potential insight into mechanism of action

Abstract: Objective: Investigation was conducted to understand the mechanism of action of diacylglycerol acyltransferase 1 (DGAT1) using small molecules DGAT1 inhibitors, compounds K and L. Design and Methods: Biochemical and stable-label tracer approaches were applied to interrogate the functional activities of compounds K and L on TG synthesis and changes of carbon flow. Energy homeostasis and gut peptide release upon DGAT1 inhibition was conducted in mouse and dog models. Results: Compounds K and L, dose-dependently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…DGAT1 and DGAT2 inhibitors were from Merck & Co., Inc., Kenilworth, NJ (23, 24). The inhibitors were suspended in DMSO and used at a final concentration of 5 μM.…”
Section: Methodsmentioning
confidence: 99%
“…DGAT1 and DGAT2 inhibitors were from Merck & Co., Inc., Kenilworth, NJ (23, 24). The inhibitors were suspended in DMSO and used at a final concentration of 5 μM.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we reported that small molecule DGAT1 inhibitors markedly alter incretin peptide release following oral lipid challenge. 21 Additionally, combination of DGAT1 inhibition with dipeptidyl-peptidase-4 (DPP-4) inhibition led to further enhancements in active GLP-1 in mice and dogs, suggesting potential combinability of DGAT1 inhibitors and DPP-4 inhibitors for treatment of metabolic diseases. 22 The DGAT1 inhibitor program at Merck was primarily built upon our initial discovery of a novel benzimidazole class of compounds bearing an acid moiety at the terminus of the structure (Figure 2).…”
mentioning
confidence: 99%
“…metabolic profile upon high fat diet feeding, including decreased body weight gain, increased insulin sensitivity, and reduced hepatic lipid accumulation (32,(37)(38)(39)(40). However, in contrast, when maintained on high fat diets, Gpat3 Ϫ/Ϫ mice exhibit weight gain in line with wild-type animals and accumulate excess hepatic lipid in the form of TG, DAG, and CE.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this difference is unclear; however, it could relate to divergent effects on enteroendocrine hormone release. Thus, although inhibition of DGAT1 is associated with suppression of GIP and robust increases in GLP-1 and the anorectic hormone peptide YY (PYY) (38,41), loss of GPAT3 results in elevated levels of circulating GIP. We were unable to discern an effect on GLP-1 levels in Gpat3 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%